On the Categorial Nature of the Generic Concept of Information - Ekaterina Petkova (Slavia Meridionalis, 2025)
This study examines the generic concept of information, interpreted broadly and analyzed in relation to its semantics. The aim is to reveal its logical status, or its categorial nature at the highest level of generalization or abstraction: entitative or attributive; ontological or constructed. Popova’s structural classification of conceptual-semantic categories is adopted as a framework and as a starting point for further considerations. The categorial nature of the generic concept of information is examined by distinguishing characteristics of its specific conceptualizations in various scientific and professional fields. Arguments are provided to support three hypotheses regarding the classification of the concept: as part of attributive ontological categories (properties, actions/activities, states, phenomena), entitative ontological categories (material and immaterial), and theoretical constructed categories.